An Outline of the Origins of Money - Heinrich Schurtz (HAU Books, 2024)
On this subject, I only knew the excellent little book by the late Schurtz"— Marcel Mauss, 1914, "Les origines de la notion de monnaie".Heinrich Schurtz's 1898 book has been a touchstone for economic historians, anthropologists, and philosophers interested in the nature and origins of money in various societies, including Georg Simmel, Max Weber, Marcel Mauss, and Karl Polanyi. Schurtz experimented with concepts about money, going beyond traditional economic paradigms. Drawing on an extensive range of archaeological and ethnographic sources, he reframed a theory of money to include its materiality, symbolic nature, relationship to forms of property, and its dual origin in "outside-" and "inside-money." While not well known today, it was important to the theorization of money in the first half of the 20th century and its innovative synthesis offers galvanizing questions and insights into how value relations are formed and how currency systems are interrelated.
Keywords: 300; Business & Economics; Economics; Theory; Business & Economics; Economic History; Social Science; Anthropology; Cultural & Social